Analysis of Integrated ANC Services on the Satisfaction and Event of High Risk in Pregnantmother in Islamic Hospital Bangil Pasuruan - Ety Diana Sulistyawati; Byba Melda Suhita; Nurdina Nurdina (Journal for Quality in Public Health, 2020)
Maternal Mortality can be prevented by early detection of high risks or complications during pregnancy, by conducting prenatal checks into available health services. The high maternal mortality rate indicates that the quality of maternal health services that are still low includes antenatal care (ANC) services. The purpose of the study was to analyze integrated anc services for satisfaction and high risk events of pregnant women at Masyithoh Bangil Pasuruan Islamic Hospital. The research design used is quantitative research with a cross sectional approach. Instrument data used questionnaire sheets using Chi Square test and Ordinal Regression. The results of the analysis of chi square test between variables ANC services integrated with satisfaction of pregnant women obtained p-value 0,000 <0,05, meaning that there is a relationship between integrated ANC services to satisfaction of pregnant women at Masyithoh Bangil Pasuruan Islamic Hospital. Whereas between integrated ANC service variables with high risk events obtained p-value 0.015 <0.05, meaning that there is a relationship between integrated ANC services to the high risk incidence of pregnant women at Masyithoh Bangil Pasuruan Islamic Hospital. Based on the results of the Ordinal Regression Test analysis shows that the most influential variable with the Integrated ANC Service at the Masyithoh Bangil Pasuruan Islamic Hospital is the variable satisfaction of pregnant women with a p-value of 0,000 <0,05. It is expected that respondents can conduct an Integrated ANC on a regular basis and the service can remain satisfactory